2009
DOI: 10.1038/nn.2385
|View full text |Cite
|
Sign up to set email alerts
|

Neurod1 is essential for the survival and maturation of adult-born neurons

Abstract: The transcriptional program that controls adult neurogenesis is unknown. We generated mice with an inducible stem cell–specific deletion of Neurod1, resulting in substantially fewer newborn neurons in the hippocampus and olfactory bulb. Thus, Neurod1 is cell-intrinsically required for the survival and maturation of adult-born neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
372
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(397 citation statements)
references
References 12 publications
22
372
2
1
Order By: Relevance
“…[60] and the present study) and (b) there is no overlap between the expression of Sox2 and Neurod1 in the DG (refs. [61,62] and our unpublished observations), the lower LI of Neurod1 þ cells when compared with Neurod1 À cells suggests that immature actively proliferating precursors (type 2a) cycle more rapidly than do neuronally committed precursors (types 2b and 3), supporting for the first time the ''cell cycle length hypothesis'' for adult neurogenic niches. Moreover, the lengthening of G 1 observed in the absence of (F-I).…”
Section: Discussionmentioning
confidence: 51%
“…[60] and the present study) and (b) there is no overlap between the expression of Sox2 and Neurod1 in the DG (refs. [61,62] and our unpublished observations), the lower LI of Neurod1 þ cells when compared with Neurod1 À cells suggests that immature actively proliferating precursors (type 2a) cycle more rapidly than do neuronally committed precursors (types 2b and 3), supporting for the first time the ''cell cycle length hypothesis'' for adult neurogenic niches. Moreover, the lengthening of G 1 observed in the absence of (F-I).…”
Section: Discussionmentioning
confidence: 51%
“…Characterization of iPSC-derived NSCs/eNPCs and neurons Western blotting analysis of NSCs/eNPCs showed a relatively low expression level of NeuroD1, indicating the absence of, or the presence of only a minor fraction of late NPCs 25 (Fig. 4a).…”
Section: Outline Of Differentiation Protocol and Nomenclaturementioning
confidence: 99%
“…One of the key molecules expressed by local astrocytes within the neurogenic niche of the adult hippocampus is Wnt3, which is required for the generation of new granule cells (7,32). Supporting the critical role of Wnt signaling in adult neurogenesis, it has been recently shown that NeuroD1, a basic helix- loop-helix transcription factor required for granule cell and olfactory neuron generation in the embryonic and adult brain, is regulated by β-catenin (11,12). We now show that Prox1, expressed in newborn but also mature granule cells selectively in the DG, is a downstream target of β-catenin-TCF/LEF signaling in the context of neurogenesis and is required for the proper differentiation and survival of newborn granule cells but not for the maintenance of granule cells after they have fully matured.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that NeuroD1, a basic helix-loop-helix transcription factor required for granule cell genesis in the embryonic and adult DG, is regulated by β-catenin-dependent signaling (9)(10)(11)(12). However, NeuroD1 is not only important for hippocampal neurogenesis but is also involved in the generation of SVZ-derived olfactory neurons (11,13,14). Thus, the network of genes regulated by the Wnt pathway to selectively generate DG granule cells in the adult hippocampus remains unknown.…”
mentioning
confidence: 99%